Relationships between heart rate and physiological parameters of performance in top-level water polo players - Galy, O.; Ben Zoubir, S.; Hambli, M.; Chaouachi, A.; Hue, O.; Chamari, K. (Biology of Sport, 2014)
The aim of this study was to measure the heart rate (HR) response of eight elite water polo players during the four 7-min quarters of the game and to check for relationships with the physiological parameters of performance ( ·VO2max, Th1vent, Th2vent). Each athlete performed a ·VO2max treadmill test and played a water polo game wearing a heart rate monitor. The game fatigue index was calculated as the ratio of the fourth-quarter HR to the first-quarter HR: HR4/HR1. The results showed a slight decrease in fourth-quarter HR compared with the first quarter, with the mean four-quarter HR equal to 79.9 ± 4.2% of HRmax. Stepwise multiple regression analysis showed ·VO2max to be the main explanatory factor of game intensity, i.e. game HR expressed in %HRreserve (R=0.88, P<0.01). We observed that higher aerobic capacity resulted in higher game intensity. We also observed a decrease in the playing intensity in the fourth quarter compared with the first, likely due to very high game involvement. We concluded that high aerobic capacity seems necessary to ensure high game intensity in water polo. This suggests that coaches should encourage their athletes to reach a minimum level of ·VO2max and that HR monitoring could be of great interest in the control of water polo training sessions.